Human Resource Management of PAI Teachers in Adjusting the Independent Curriculum in Elementary Schools: Challenges and Solutions - Akmalia, Agustin Ziadatul; Mushokhiyah, Shishi (Proceedings Series on Social Sciences & Humanities, 2025)
This article discusses challenges and solutions related to human resource management (HR) for Islamic Religious Education (PAI) teachers in adapting to the implementation of the Independent Curriculum at the elementary school level in Indonesia. The Independent curriculum introduces a more flexible, student-centered approach that emphasizes differentiated learning, project-based instruction, and character development. However, PAI teachers often face various obstacles in this transition process. These include inadequate training related to curriculum changes, limited access to educational technology, and difficulties in transitioning from traditional teacher-centered teaching methods to a more active, contextual, and collaborative approach as required by the new curriculum. This study aims to evaluate effective HR strategies that can support PAI teachers in adopting the Independent Curriculum successfully. The findings show that intensive and ongoing training programs, structured mentoring between experienced and novice teachers, and gradual integration of technology into classroom practice significantly improve teacher readiness and competence. Furthermore, institutional support, professional development opportunities, and adequate resource allocation are essential to ensure that the implementation of the Independent Curriculum in Islamic religious education is not only procedural, but also leads to meaningful and transformative changes in teaching and learning. This article underscores the importance of aligning HR management with pedagogical reforms to achieve long-term education improvement.